AUTOMATIC INDICATOR SYSTEM FOR WSN UTILIZATION IOT STUFFING MACHINE INFUSION WATER VOLUME DETECTOR - Harahap, Ricky Ramadhan; Kurniawan, Fahmi (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: The use of intravenous infusion sets has greatly increased, but there are some problemscaused by various causes, namely negligence by nurses, lack ofsupervision by the patient's family and from the actions of the patient who caninterfere with the infusion system. The urgency expected to be madeone of the effective and efficient solutions in the automation system for detecting the volume of infusion water and this innovation is expected to help nurses in monitoring intravenous fluid replacement, reducing the risk of delays in replacing intravenous fluids for patients and the public to know the system is running out of infusion water with the sound of an alarm/buzzer. The purpose of this study was to design an infusion control device by detecting the volume of infusion water based on the weight of the infusion using a Wireless Sensor Network. The Wireless Sensor Network used by the load cell sensor functions to detect the weight value of the infusion water in the infusion bag. The buzzer becomes an indicator indicating that the infusion bag is ready to be replaced and also through the Stuffing Machine the Internet of Things will inform the nurse via the Telegram application to inform that the infusion bag is worth replacing. So that nurses can monitor the process of detecting the volume of infused water remotely. Keywords: Arduino, Blind Detector, Indicator system, Prototype  Abstrak: Penggunaan infus set intravena sangat meningkat, namun ada beberapa masalah yang disebabkan oleh berbagai penyebab yaitu kelalaian oleh perawat, kurangnya pengawasan oleh keluarga pasien dan dari tindakan pasien yang dapat menghambat sistem kerja pada infus. Urgensi yang diharapkan agar dapat dijadikan salah satu solusi yang efektif dan efisien dalam sistem otomatisasi pendeteksian volume air infus dan inovasi ini diharapkan bisa membantu perawat dalam pemantauan penggantian cairan intravena, mengurangi resiko keterlambatan penggantian cairan intravena bagi pasien dan masyarakatpun mengetahui sistem habisnya air infus dengan bunyinya alarm/buzzer. Tujuan penelitian ini menghasilkan rancangan alat pengontrolan infus dengan cara mendeteksi volume air infus berdasarkan berat dari air infus dengan menggunakan Wireless Sensor Network. Wireless Sensor Network yang digunakan sensor load cell berfungsi untuk mendeteksi nilai berat air infus yang ada pada kantung infus. Buzzer menjadi sebuah indikator yang menandakan bahwa kantung airinfus sudah layak diganti dan juga melalui Stuffing Machine Internet Of Things akan menginformasikan ke perawat melalui aplikasi Telegram menginformasikan kantung air infus sudah layak diganti.  Sehingga perawat dapat memonitoring proses pendeteksi volume air infus dari jarak jauh.. Kata kunci: Infused Water; Load Cells; Prototypes; Stuffing Machine Internet Of Things;                  Volume